The Contribution of Islamic Law in Resolving Aceh Customary Disputes Over Joint Property Division Due to Divorce - Afrizal, Afrizal (Al-Fikrah, 2023)
In Aceh, joint property is referred to as "heureta sihaurekat". Among the scholars of the four madhhabs, the Hanafi, Maliki, and Hanbali allow joint property in the form of syirkah mufawadhah abdan, while al-Shafi'i rejects joint property associated with syirkāh. Based on initial interviews with customary leaders, it is found that all properties owned by a husband and wife at the time of divorce have equal rights between the husband and wife, despite any discrepancies in amount. Additionally, it does not consider who, whether husband or wife, was the earning member. The research questions in this study are: What is the model of joint property division due to divorce according to Aceh customary law? How does the existence of Aceh customary law decisions regarding the division of joint property due to divorce from the perspective of Islamic Law? This study uses a qualitative research method with a normative-empirical type by conducting observations, interviews, and documentation and analyzing using a descriptive method. In the pattern of division, the community leaders and village heads resolve it through mediation and discussion, thus distributing the property according to agreement, either equally, more to the wife, or even in thirds. From the perspective of Islamic law, the division of joint property conducted by the Aceh customary court can be associated with maslahāh (public interest) and 'urf (custom) that does not contradict sharia. In this case, the maslahāh that can be associated with community practice is maṣlaḥah hajiyat (basic necessity) and is considered a valid custom (al-'urf al-sahīh), and in distributing the property, a system of justice and consent from both parties is applied.